1977
DOI: 10.1073/pnas.74.7.2909
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and distribution of a cell surface glycoprotein and its interaction with other membrane components

Abstract: Fluorescence photobleaching recovery and immunofluorescence methods have been used to study the lateral mobility and topographical distribution of a major cell surface glycoprotein (CSP). Both endogenous CSP and fluorescent-labeled exogenous CSP been identified on the surface of many fibroblastic cells (1, 2). The amount of this protein decreases substantially after transformation (2). Designated cell surface protein (CSP) (3) or large, external, transformation-sensitive (LETS) protein (4), this protein has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
1

Year Published

1978
1978
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(27 citation statements)
references
References 17 publications
4
22
1
Order By: Relevance
“…FN crosslinks with itself and other proteins through disulfide links (9,45). FN on cell surfaces is known to be immobile and may serve as an anchorage point for cell attachment (44). Thus, FN in the subendothelium may be an important structural component which plays a role in endothelial cell attachment and adhesiveness under normal conditions and after injury to the vascular wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FN crosslinks with itself and other proteins through disulfide links (9,45). FN on cell surfaces is known to be immobile and may serve as an anchorage point for cell attachment (44). Thus, FN in the subendothelium may be an important structural component which plays a role in endothelial cell attachment and adhesiveness under normal conditions and after injury to the vascular wall.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast cultures contain fibrils which stain for both FN and collagen when examined by immunofluorescence microscopy (17). The basis for this congruence of location may be the recently described noncovalent interactions of FN with other FN molecules (44) and with collagen (18). FN crosslinks with itself and other proteins through disulfide links (9,45).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that fibronectin fibers do not impede the diffusion of lipid probes and cell surface antigens [28]. Concanavalin A, however, is immobilized by binding directly to immobile fibronectin fibers m1.…”
Section: Modulation Of Lipid and Protein Mobilitiesmentioning
confidence: 99%
“…For example, the acetylcholine receptor (AChR) localized at neuromuscular junctions and in patches on myotubes (7,8), and frbronectin on the surface of cultured fibroblasts (9) .…”
mentioning
confidence: 99%